Vacío existencial y riesgo suicida en pacientes con trastorno de personalidad borderline - Valdivia-Pareja, Álvaro Eduardo (2007)
The purpose of this study is to describe the characteristics that borderline personality disorder patients show in existential emptiness and suicidal risk. The instruments used were the Purpose in Life Test (PIL), Suicide Intent Scale (SIS) and the Borderline Personality Disorder Diagnosis Protocole. The non-probabilistic sample consisted of 42 participants, 32 females and 10 males, whom, at the time of the study, were assisting to the Psychology and Diagnosis Service of a National Psychiatric Hospital of Lima. The method was descriptive, with a comparative-descriptive design. The results show that the PIL and SIS scales prove to have adequate reliability and construct validity.